Dissertation councils of the future: 5 × 7 ≠ quality - V. G. Sadkov; D. V. Aronov; A. V. Koskin; P. N. Mashegov (Высшее образование в России)
This article analyzes the situation prevailing in the system of preparation and thesis defense in Russia. The authors offer their own concept of improving the system of training of highly qualified personnel in Russia.